2009
DOI: 10.1007/s10799-009-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying fall-related injuries: Text mining the electronic medical record

Abstract: Unintentional injury due to falls is a serious and expensive health problem among the elderly. This is especially true in the Veterans Health Administration (VHA) ambulatory care setting, where nearly 40% of the male patients are 65 or older and at risk for falls. Health service researchers and clinicians can utilize VHA administrative data to identify and explore the frequency and nature of fallrelated injuries (FRI) to aid in the implementation of clinical and prevention programs. Here we define administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…According to Monica Chiarini Tremblay et al (2009)it can be easily comprehended and applied. For this, around hundred papers from three leading journals spread over last ten years have been considered.…”
Section: Review Of Literature For Application With Data Mining Imentioning
confidence: 99%
See 1 more Smart Citation
“…According to Monica Chiarini Tremblay et al (2009)it can be easily comprehended and applied. For this, around hundred papers from three leading journals spread over last ten years have been considered.…”
Section: Review Of Literature For Application With Data Mining Imentioning
confidence: 99%
“…In a country of over 1.1 billion people, the healthcare system will have to innovate to double the utilization of its existing resources so as to reach a stage available in developing countries (Aqueel Ahmed et al 2012). According to Monica Chiarini Tremblay et al (2009) "telemedicine is one such innovative technology", and "if used effectively can double utilization of scarce human resources" (Leigh Turner et al 2007). If telemedicine models are integrated with the healthcare model, such models may become viable.…”
mentioning
confidence: 99%
“…There are many interesting fields of research such as detection of similarities between patent documents and scientific publications (Magerman et al 2010); examining mobile learning trends (Hung and Zhang 2011); discovering a multi-functional metal-binding glycoprotein that exhibits many biological functions of interest to many researchers from the fields of clinical medicine, dentistry, pharmacology, veterinary medicine, nutrition and milk science (Shimazaki and Kushida 2010); identifying fall-related injuries in electronic medical record (Tremblay et al 2009); mining business policy texts for discovering process models (Li et al 2010); discovering knowledge by opinion mining from noisy text data (Dey and Haque 2009); tracking what people are saying, finding influencers, and using many social network analytic tools to analyze the underlying social networks embedded within the blogosphere (Macskassy 2011) and (Huang et al 2011) and with emails via clustering and pattern discovery (Manco et al 2008); identifying the anomaly cases for knowledge discovery from the warranty and service data in the automotive domain (Rajpathak et al 2011); discovering frequent musical patterns (motifs) that is a relevant problem in musicology (Jiménez et al 2011). In Biology, text mining has new challenges as can be seen in Dai et al (2010); a good example of text mining on language recognition can be seen in Al-Jumaily et al (2011), where Arabic, the most widely spoken language in the Arab World is identified on the web.…”
Section: Text Miningmentioning
confidence: 99%
“…Previously unstructured data has been used for a range of purposes such as diagnosis detection (e.g. Meyste, 2006;Suzuki, 2008;Liao, 2010), decision support (Tremblay, 2009), and temporal investigation of adverse drug reactions (Eriksson, to appear 2014). Structured EPR data will primarily contain diagnoses relevant to the current hospitalization, whereas free text will contain additional information about adverse drug reactions and the general health status of the patient.…”
Section: Introductionmentioning
confidence: 99%